Development of agar diffusion method for dosage of gramicidin - Ana Gabriela Reis Solano; Larissa de Melo Campos Sousa Pereira; Míriam de Fátima Vianna Leonel; Elzíria de Aguiar Nunan (Universidade de São Paulo, 2011)
Gramicidin, an antimicrobial peptide active against Gram positive bacteria, is commonly used in pharmaceutical preparations for topical use. Considering that only the turbidimetric method has been described in the literature, the present study sought to develop and validate an agar diffusion method for the dosage of gramicidin. The method was developed and validated using the Kocuria rhizophila ATCC 9341 as a test microorganism. Two designs were used: a 3x3 parallel-line model, and a 5x1 standard curve. The validation demonstrated that the method follows the linear model (r²= 0.994), presenting a significant regression between the zone diameter of growth inhibition and the logarithm of the concentration within the range of 5 to 25.3 µg/mL. The results obtained for both designs were precise, having a relative standard deviation (R.S.D.) for intra-day precision of 0.81 for the 3x3 assay and 1.90 for the 5x1 assay. For the inter-day precision, the R.S.D. was 1.35 for the 3x3 and 2.64 for the 5x1. The accuracy was verified and results confirmed to be accurate, having a tolerance interval of 95%, which lay within permitted limits and appropriate trueness. In addition, the method was considered selective, with limit of detection and upper and lower limits of quantification of 2.00, 5.00 and 25.3 µg/mL, respectively. No difference in precision between the designs used in the agar diffusion method was evident (p>0.05). The method proved to be appropriate for the microbiological dosage of the raw material gramicidin. A gramicidina, um peptídeo antimicrobiano ativo contra bactérias Gram positivo, é utilizada em preparações farmacêuticas de uso tópico. Neste trabalho procurou-se desenvolver e validar outro método para o doseamento de gramicidina tendo em vista que somente o método turbidimétrico é descrito. O método de difusão em ágar foi desenvolvido e validado utilizando como microrganismo teste Kocuria rhizophila ATCC 9341. Foram utilizados dois delineamentos: retas paralelas 3x3 e curva padrão 5x1. A validação demonstrou que o método segue o modelo linear (r²= 0,994) havendo regressão significativa entre o diâmetro dos halos de inibição e o logaritmo da concentração na faixa de 5,00 a 25,3 µg/mL. Os resultados obtidos por ambos os delineamentos foram precisos apresentando desvio padrão relativo (DPR) para precisão intra-dia de 0,81 para ensaio 3x3 e de 1,90 para ensaio 5x1. Para a precisão inter-dias o DPR foi de 1,35 para 3x3 e de 2,64 para 5x1. A exatidão foi verificada e os resultados foram exatos apresentando intervalo de tolerância a 95% dentro dos limites permitidos e veracidade adequada. O método foi seletivo com limites de detecção e quantificação inferior e superior iguais a 2,00, 5,00 e 25,3 µg/mL, respectivamente. Não foi observada diferença entre a precisão dos delineamentos empregados no método de difusão em ágar (p>0.05). O método se mostrou adequado para a dosagem microbiológica de gramicidina matéria-prima.